(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2018)
Cloud computing has evolved as one of the most powerful approach in the IT industry. It provides so many advantages like minimum expense, great performance, availability of resources, due to which it is considered as revolution amongst organizations. In cloud computing various resources are shared through network in open environment so that the user can access the information from anywhere, but there exist the issues of security and privacy of user and its information. It also provides a broad study on the issues and challenges of security .Growth of cloud computing is mainly decreased due to these concerns and challenges. Even though there is secure Homomorphic encryption there lays certain security issues and attacks with it. This paper deals with the analysis of security issues on cloud computing and finding counter measures on those issues. The fundamental security issues such as confidentiality, integrity, availability, trust and audit and compliance is analyzed and the impact on each characteristics of cloud computing as well as the third party control has been examined.